THE EFFECT OF SOCIAL MEDIA MARKETING AND WORD OF MOUTH ON PURCHASE DECISIONS AT COFFEE SHOPS IN MANADO - Adolf, Lapian P. M; Lapian, Joyce S.L.H.V.; Tulung, Joy E. (Universitas Sam Ratulangi, 2020)
This study aims to examine if there are significant effect of social media and word of mouth on purchase decisions at coffeeshops in Manado, the object of this study are local coffee shops in Manado. This study is a quantitative research by distributing questionnaires using Likert Scale. The sample in this research is consisting of 100 respondents. The purposive sampling was apllied in this research regarding to obtain information according to customers who have purchased at local coffee shops that already do social media marketing. This research is a comparative test which are social media and word-of-mouth has simultaneously effects on consumer purchase decision as the dependent variable and social media and word of mouth as one of independent variables partially affects consumer purchase decision in Local Coffee shops positively. Local Coffee shops need to create a competitive advantage in order to win market of Local Coffee shops.Keywords: coffeshop, marketing, word of mouth, social media, purchase decision